Burden of Illness in Adult Survivors of Childhood Cancers: Findings from a Population-based National Sample - Dowling, Emily (2010)
PURPOSE: The number of adult survivors of childhood cancer in the U.S. is increasing due to effective treatments and improved survival. The purpose of this study was to use a national, population-based sample to estimate the burden of illness in adult survivors of childhood cancer. METHODS: A total of 410 adult survivors of childhood cancer and 294,641 individuals without cancer were identified from multiple years of the National Health Interview Survey. Multiple measures of burden, general health, and lost productivity were compared using multivariate regression analyses including: logistic, polytomous logit, proportional odds, and linear models. RESULTS: Controlling for the effects of age, gender, race/ethnicity, and survey year, adult survivors of childhood cancer reported poorer outcomes across the majority of general health measures and productivity measures than individuals without cancer. Survivors were more likely to report their health status as fair or poor (24.3% vs. 10.9%; p<0.001); having any health limitation in any way (12.9% vs. 3.4%; p<0.001); being unable to work due to health problems (20.9% vs. 6.3%; p<0.001); and being limited in the amount/kind of work due to health problems (30.9% vs. 10.6%; p<0.001). When categorized by time since diagnosis, cancer survivors had poor health outcomes in every time interval, with the greatest limitations in the initial 4 years following diagnosis and 30 or more years after diagnosis. CONCLUSION: Adult survivors of childhood cancers have poorer health outcomes and more health limitations than similar individuals without cancer across multiple measures.